Executive Committee Minutes 2010-09-23 - Academic Senate:::::::::
Discussion of RTP requirements for transcribing qualitative comments, Adding Senate Budget Subcommittee to by-laws, Faculty Retreat Discussion, Curricular item to the Ex Com and new EPC forms, New Learning Objectives for GE Areas A and C, FSAC Feedback on Mandatory Holds for Advising Resolution, Initial Report and Recommendations re: 16th Unit for Lecturers